The impact of the COVID-19 pandemic on presentations to health services following self-harm: a systematic review - Steeg, S; John, A; Gunnell, D; Kapur, N; Dakel, D; Schmidt, L; Knipe, D; Arensman, E; Hawton, K; Higgins, J; Eyles, E; Macleod-Hall, C; et al. (Cambridge University Press, 2022)
Background Evidence on the impact of the pandemic on healthcare presentations for self-harm has accumulated rapidly. However, existing reviews do not include studies published beyond 2020.